The Impact of Technology on Education: A Case Study of Schools - Kiong, Jairo Florinio (Pusat Studi Pembangunan dan Pemberdayaan, 2022)
The current research examines the effects of integrating technology into K-12 classrooms specifically in rural school environments regarding its advantages and disadvantages, effects on student attentiveness or interest, and effect for students’ equality in school and teaching methods. This paper thus employs a case study to examine how digital means have impacted on classroom interactions and made education more diverse to rural learners. The study shows that the extent to which technology increases students’ interest and helps manage students’ diverse learning needs is great but the implementation is constrained by infrastructural deficiencies, insufficient professional development, and lack of preparedness. Moreover, inequalities are rising with ever more diverse educational ICT access outside the school environment deepening the existing inequalities. The study shows that technology integration can be best understood as a reconstructive-process level and thus requires attention to infrastructural issues, pointed continuation of the teacher education program, and a fair distribution of the digital assets. Thus, the study calls on all the educational stakeholders especially policymakers, educational institutions and local authorities to embrace full implementation and support the use of technology to foster education for children in rural areas.